2011
DOI: 10.1093/cid/cir613
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Novel Point-of-Care Cryptococcal Antigen Test on Serum, Plasma, and Urine From Patients With HIV-Associated Cryptococcal Meningitis

Abstract: This novel dipstick test has the potential to markedly improve early diagnosis of CM in many settings, enabling testing of urine in patients presenting to health care facilities in which lumbar puncture, or even blood sampling, is not feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
227
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(246 citation statements)
references
References 20 publications
7
227
0
5
Order By: Relevance
“…The lateral flow assay for cryptococcal antigenemia has been validated as a good diagnostic screening test for cryptococcosis and could be integrated into primary health care, to detect the disease in patients with CD4 counts below 100 cell/ uL pre-ART 36 . There is also need for intensified community mobilization and sensitization on diseases such as TB, cryptococcal meningitis and Kaposi's sarcoma to raise the index of suspicion among communities to enable early treatment seeking.…”
Section: Discussionmentioning
confidence: 99%
“…The lateral flow assay for cryptococcal antigenemia has been validated as a good diagnostic screening test for cryptococcosis and could be integrated into primary health care, to detect the disease in patients with CD4 counts below 100 cell/ uL pre-ART 36 . There is also need for intensified community mobilization and sensitization on diseases such as TB, cryptococcal meningitis and Kaposi's sarcoma to raise the index of suspicion among communities to enable early treatment seeking.…”
Section: Discussionmentioning
confidence: 99%
“…Early demonstration studies have shown that the LFA has a high level of agreement with conventional antigen tests when performed on urine and serum samples (16). The LFA has been FDA approved for use on CSF samples, but published data on the sensitivity and specificity compared to those of the CLAT and culture are limited (1,17).…”
Section: Ryptococcal Meningitis (Cm) Is a Frequent Hiv-related Oppomentioning
confidence: 99%
“…The simple and inexpensive cryptococcal polysaccharide antigen (CRAG) test has excellent sensitivity and specificity for detection of CRAG in serum, plasma, and CSF (Jarvis et al 2011b). Cryptococcal antigenemia, indicating early dissemination from the lung, precedes symptomatic meningitis by weeks to months (French et al 2002), with reported prevalence in cohorts of HIV-infected patients with CD4 ,100 cells/mL ranging between 2% and 21% Jarvis et al 2011a).…”
Section: Prevent CM Unmasked By Art Using Crag Screening and Preemptimentioning
confidence: 99%